2015
DOI: 10.1016/j.mspro.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Open–Cell Aluminum Foams Obtained through Infiltration Processes

Abstract: This work reports the fabricating of open-cell Al foams which were manufactured through infiltration processes employing a device with controlled atmosphere for the fusion and infiltration processes of the metal, which is separate from the heating furnace. The device allows controlling its internal atmosphere with an inert gas to protect the metal of the fast oxidation, avoiding the employment of a controlled atmosphere furnace (a furnace of this kind incorporate the heating and the control atmosphere systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 5 publications
3
13
0
Order By: Relevance
“…This is in full harmony with what is stated in other studies [21,28]-that the tiny strut thickness and the high level of the porosity can result in a degraded mechanical behavior. Under applied compressive or tensile stresses, the foam material starts to fail by the cracking of the thin struts that provide the weakest points for crack initiation and propagation.…”
Section: Compressive Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…This is in full harmony with what is stated in other studies [21,28]-that the tiny strut thickness and the high level of the porosity can result in a degraded mechanical behavior. Under applied compressive or tensile stresses, the foam material starts to fail by the cracking of the thin struts that provide the weakest points for crack initiation and propagation.…”
Section: Compressive Propertiessupporting
confidence: 91%
“…The previous studies [13,21] focused on melt processing of metallic foam and reported that the melt infiltration using the NaCl particles with an average particle size smaller than 1 mm is extremely difficult. Decreasing the size of the particle space holder results in an elevated pressure opposing the infiltration due to the capillary pressure and the friction between the melt and NaCl Reproducing the same cellular morphology of different metals of Al, Mg, and Al-SiC that already display high diversity in melt characteristics (viscosity, fluidity, density, etc.)…”
Section: Microstructurementioning
confidence: 99%
“…By solidification of these metal melts, a heterogeneous system is formed consisting of metal and sodium chloride particles. Various technologies are used in the production of porous materials, [17], [18], [19], [20]. Other research preffered instead of sodium chloride particles of sand bound, for example, by furan resin or ceramic particles bound by gypsum.…”
Section: Process Of Production Of Porous Aluminium Materialsmentioning
confidence: 99%
“…The commercially available salt (NaCl), a white crystalline, density 2.16 g.cm -3 , melting point 804 ℃, boiling point 1413 ℃, is soluble in water [5]. The commercially available salt particles are baked at lower temperatures about 150 ℃ for 12 hours, removal crystal water, avoid salt particles burst from the broken, so the gap between particles that the metal.…”
Section: The Preparation Process Of Air Pressure Infiltration Processmentioning
confidence: 99%